Local environmental fiscal expenditures, industrial structure upgrading, and carbon emission intensity - Zhang, Xuesheng; He, Shouchao; Ma, Lindong (Frontiers in Environmental Science, 2024)
To realize the development goals of environmental governance and low-carbon emission reduction, the effect of local environmental protection fiscal expenditure on carbon emissions needs to be assessed. This paper utilizes the panel data of 30 provinces in mainland China except Tibet from 2007 to 2019 and empirically examines the baseline effect, the mechanism, the nonlinear effect, and the spatial spillover effect of the local environmental protection fiscal expenditures affecting the intensity of carbon emissions by using the fixedeffects model, the FGLS model, the threshold panel model, and the spatial Durbin model. The results indicate that local environmental fiscal expenditure significantly lowers carbon emissions, generating a carbon reduction effect, and this finding remains robust under various checks; the mechanism analysis reveals that local environmental fiscal expenditure facilitates industrial structure upgrading, thereby indirectly producing a carbon reduction effect; the threshold analysis shows that the carbon reduction effect of local environmental fiscal expenditure exhibits a diminishing marginal tendency, and as the industrial structure continues to upgrade, the carbon reduction effect of local environmental fiscal expenditure displays an "Inverted U-shaped" pattern; the spatial analysis demonstrates that local environmental fiscal expenditure and carbon emissions have positive spatial autocorrelation, and local environmental fiscal expenditure in one region will induce a decline in carbon emissions in neighboring regions through spatial spillover effect. Based on the above results, this paper puts forward policy suggestions in terms of constructing a reasonable growth mechanism for local environmental protection financial expenditures, creating an ecological environment for low-carbon transformation, and constructing a reasonable regional coordination mechanism for carbon emission reduction.